Peningkatan Kemandirian dan Hasil Belajar Peserta Didik Melalui Implementasi E-Modul Interaktif IPA Terpadu Tipe Connected Pada Materi Energi SMP/MTs - Roza Linda*; Zulfarina Zulfarina; Mas’ud Mas’ud; Teja Pratama Putra (Jurnal Pendidikan Sains Indonesia, 2021)
Learning process during Covid-19 pandemic should have been anticipated because the 21st century and IR 4.0 era obligated teachers to facilitate student-centered learning and used of IT-based teaching materials, according students' needs and characteristics. Although, often found unqualify teaching materials. So, learning outcomes' target and students self' learning aspect will be obstructed. The research aimed to improve students self' learning and learning outcomes by implementing e-module. The research was final step of previous research (R D) which has produced a valid e-module. The research was the quantitative descriptive method. The research type used was quasi experimental with one group pretest-posttest design. The sample technique used was purposive sampling with 30 students of SMPN 2 Kandis as sample. The data collection technique was used questionnaires of students self' learning and tests of learning outcomes as instruments. Data was analyzed by descriptive statistics (percentage) for questionnaires, and paired sample t-test and N-Gain for tests. The results showed that students self' learning increase after using e-module from 64.69% to 81.04% (medium-high category). Also with students learning outcomes, obtained t0 = 7.55 ≥ ttab = 1.69 (dk = 29, α = 0.05) which means there was an increase. Based N-Gain = 0.76, the increasing in medium category. Thus, the implementation of integrated sains e-module with connected type on energy subject can be an alternative to improve students self' learning and learning outcomes